PALLIATIVE CARE AND INTEGRATED PALLIATIVE CARE IN ONCOLOGY: STRATEGIES FOR PROMOTING QUALITY OF LIFE IN CANCER PATIENTS - Monteiro, Nathália; Meneses, Anne Gabrielle Silva; Garcia, Maria Isabele Barros; Correa, Sara Cristina Santos; Araujo, Vitória Maria Lobo; Moraes, Bruna Nunes; Agostinho, Ana Beatriz Alencar; Ferreira, Diogo Milioli (CIPEEX, 2025)
Introduction: The integration of palliative care into cancer treatment, especially through integrated palliative care, is essential to improve the quality of life of cancer patients. This early and multidisciplinary approach provides monitoring from the initial stages of the disease. It also promotes humane care, encompassing emotional, social, and spiritual aspects. Furthermore, it challenges the misconception that palliative care is limited to end-of-life care, demonstrating that it can and should complement disease-modifying therapies.Objective: To analyze the relevance of palliative care, especially integrated palliative care, in the care of cancer patients, with a focus on improving quality of life, symptom control, and emotional support for both patients and their families.Methodology: An integrative literature review was conducted, searching the PubMed database using the descriptors "Palliative Care," "Integrated Palliative Care," "Cancer" and "Quality of Life," Five articles published between 2019 and 2024 were included, comprising randomized clinical trials, systematic reviews, and observational studies. Duplicate articles, studies outside the scope, or articles published before 2019 were excluded.Results: Evidence suggests that early palliative care improves the management of physical symptoms, such as pain, fatigue, and dyspnea, while also contributing to the reduction of anxiety and depression. Patients monitored by multidisciplinary teams report higher satisfaction with treatment and receive better support for their families throughout the illness. Another relevant finding is the reduction of unnecessary hospitalizations and aggressive end-of-life interventions, benefiting both patient experience and healthcare system organization. Integrated models positively impact resource allocation, enhance communication between staff and patients, and support therapeutic decisions aligned with individual values and preferences.Conclusion: Palliative and integrated care, when implemented early, significantly improve the quality of life of cancer patients. However, challenges remain, including cultural barriers, a shortage of trained professionals, and unequal access across regions. Therefore, investing in continuous professional training, raising societal awareness, and implementing consistent public policies are essential to expand coverage and consolidate this practice in oncology. Strengthening these strategies points toward a future where cancer care is more dignified, compassionate, and patient-centered.